Preparation method and application of black fiber winding tape roll

By deeply cleaning the basalt fibers, removing metal impurities and strengthening the activity of the basalt fibers, and surface modification with coupling agents and nanoparticles, the problem of performance degradation of existing hydrogen transport pipeline reinforcement layer materials in long-term use is solved, and the high mechanical properties and long-term durability of the black fiber winding belt is achieved.

CN118955962BActive Publication Date: 2025-03-18CANGZHOU MINGZHU PLASTIC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411418624.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-03-18
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing hydrogen transport pipeline reinforcement layer materials have problems such as decreased chemical stability, physical aging, thermal aging and environmental factors in long-term use, resulting in performance degradation and safety hazards.

Method used

The surface optimization of basalt fibers was carried out using deep surface cleaning, metal impurity removal and activity reinforcement treatment, and then the stable chemical bond structure was formed through coupling agent-mediated surface modification and nanoparticle grafting to improve the mechanical properties and durability of the fibers.

Benefits of technology

It significantly improves the comprehensive performance of the mysterious fiber winding belt, including improving mechanical strength, chemical resistance, heat resistance and fatigue resistance, extending the service life of the material, and reducing safety hazards caused by static electricity accumulation and release.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118955962B_ABST
    Figure CN118955962B_ABST
Patent Text Reader

Abstract

The present invention provides a preparation method and application of a black fiber winding tape roll, belonging to the technical field of composite material preparation. The preparation method of the black fiber winding tape roll of the present invention comprises the following steps: S1 deep surface cleaning; S2 fiber surface optimization treatment; S3 preparation of coupling agent solution; S4 coupling agent mediated surface modification; S5 nanoparticle grafting; S6 black fiber ribbon forming; S7 resin liquid preparation; S8 coating and rolling; by winding the prepared black fiber winding tape on the circumferential outer wall of the inner lining layer of the composite pipe as a reinforcement layer, the necessary mechanical support is provided for the composite pipe, ensuring the reliability and durability of the composite pipe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material preparation, and in particular to a preparation method and application of a black fiber winding tape roll. Background Art

[0002] In the composite pipeline for hydrogen gas, the inner liner is in direct contact with the transport medium. Although the inner liner can provide good chemical stability and low permeability to safely transport hydrogen, it usually does not have sufficient mechanical strength and rigidity to resist internal and external pressures. A reinforcement layer is required to be set on the inner liner. The role of the reinforcement layer is to increase the overall structural strength of the pipeline so that it can withstand various mechanical stresses that may be encountered during transportation, such as bending, torsion and compression. In a high-pressure environment, without the support of the reinforcement layer, the inner liner may rupture or other forms of structural failure due to excessive internal pressure. The reinforcement layer helps the inner liner maintain its integrity by dispersing and absorbing part of the pressure, thereby extending the service life of the pipeline. The reinforcement layer also helps to protect the inner liner from external environmental factors such as temperature changes, chemical corrosion or physical damage. This is particularly important because hydrogen transportation pipelines are often laid in a changeable external environment, and hydrogen may generate heat when flowing or compressed at high speed. The reinforcement layer helps maintain the thermal stability of the pipeline and prevents the performance degradation of the lining material due to temperature increase. The reinforcement layer not only provides the necessary mechanical support, but also ensures the reliability and durability of the system, which is essential for the safe and efficient transportation of hydrogen.

[0003] At present, the mainstream reinforcement layer materials on the market are carbon fiber composites and glass fiber composites. These materials are applied to pipes by winding, weaving or laying to enhance the comprehensive performance of the pipes; for carbon fiber composites: Advantages: It has extremely high strength and stiffness, light weight, can effectively reduce the overall weight of the structure, and is very suitable for application scenarios that require lightweight. Disadvantages: high cost, complex production process, and difficult repair and maintenance. In addition, the heat resistance of carbon fiber is not as good as that of metal materials, and additional thermal management measures may be required to adapt to high temperature environments. Glass fiber composites: Advantages: Compared with carbon fiber, it has lower cost, good strength and rigidity, and also good chemical resistance. Disadvantages: Strength and rigidity are usually lower than carbon fiber, and wear resistance and impact resistance are not as good as high-strength steel. It is not suitable for extreme mechanical load conditions.

[0004] In recent years, basalt fiber has gradually been regarded as an ideal hydrogen pipeline reinforcement material due to its excellent mechanical properties, good chemical resistance and high temperature resistance, as well as low cost. Although basalt fiber shows many excellent performance characteristics, there is still insufficient data on its long-term durability in specific hydrogen transmission environments, which are mainly manifested as follows:

[0005] Long-term effects of chemical stability: Although basalt fibers exhibit good chemical resistance in the short term, their chemical structure will gradually change when exposed to high concentrations of hydrogen and other potential chemicals over a long period of time. This change leads to a decrease in the mechanical properties of the fiber, such as a reduction in strength and toughness. In addition, hydrogen penetration into the material may cause microstructural damage, such as the formation of microcracks, further affecting the overall performance of the material.

[0006] Physical aging issues: Basalt fibers will experience physical aging when working in a high-pressure environment for a long time, especially under variable pressure conditions. This includes the accumulation of microscopic damage caused by fatigue and cyclic loading, which leads to a gradual decrease in material performance. Physical aging may also manifest as a decrease in the bond strength between the fiber and the matrix material, affecting the stability and sealing of the overall structure.

[0007] Thermal aging and thermal stability: Hydrogen pipelines may be subject to temperature fluctuations during use, especially in areas with high-temperature operations or large changes in ambient temperature. Although basalt fiber has good high-temperature resistance, long-term high-temperature exposure may cause changes in its physical and chemical properties. Thermal aging may cause fiber strength loss, modulus changes, or oxidation reactions, further affecting the long-term stability of the material.

[0008] Impact of environmental factors: Environmental factors, such as UV radiation, humidity and salt spray, also have a negative impact on the long-term performance of basalt fibers. For example, UV radiation may destroy the chemical bonds on the fiber surface, resulting in performance degradation. Changes in humidity affect the bonding between the fiber and the resin, while salt spray may accelerate the chemical corrosion process.

[0009] As a highly flammable gas, hydrogen can cause safety hazards due to the accumulation and release of static electricity during transportation; static electricity accumulates on the surface of the pipeline due to friction and separation. The flow rate and flow rate of hydrogen and the roughness of the inner surface of the pipeline will affect the speed and amount of static electricity generation. Static electricity that accumulates to a certain level may cause discharge in the hydrogen environment, which is particularly dangerous in a mixed environment containing oxygen, because even a tiny spark may trigger a hydrogen explosion. Therefore, it is crucial to ensure that static electricity in the hydrogen transportation system can be safely released.

[0010] Therefore, considering the application requirements of hydrogen pipeline systems in high pressure and dynamic environments, as well as the limitations of existing reinforced materials, it is particularly important to develop a new composite material. Summary of the invention

[0011] The purpose of the present invention is to address the above-mentioned problems in the prior art and to propose a method for preparing a black fiber winding tape roll and an application of the black fiber winding tape roll.

[0012] The purpose of the present invention can be achieved by the following technical solutions: A method for preparing a black fiber winding tape roll, comprising the following steps:

[0013] S1 Deep surface cleaning: Use a cleaning solution containing a non-ionic surfactant to clean the basalt fiber raw yarn, and the cleaning temperature is controlled at 50-60°C; after the cleaning operation is completed, rinse with deionized water to obtain cleaned basalt fiber yarn;

[0014] The nonionic surfactant is at least one of polyoxyethylene alcohol, polyethoxylated nonanoic acid ester and dodecyl polyoxyethylene ether;

[0015] This involves deep surface cleaning of the basalt fiber strands using a cleaning solution containing a non-ionic surfactant. This step is critical for the following reasons:

[0016] Removal of impurities and surface contaminants: During the manufacturing process, basalt fibers may absorb or be contaminated with various impurities, including dust, grease, and other industrial residues. These contaminants will affect the performance of the fiber, especially in subsequent chemical treatments and physical performance. The use of surfactants can effectively remove these impurities and ensure the cleanliness of the fiber surface.

[0017] Selection of non-ionic surfactants: Polyoxyethylene alcohol: It has good wetting and cleaning ability, can form a uniform wetting layer on the fiber surface, and increase the separation between pollutants and fibers.

[0018] Polyethoxylated Nonanoic Acid: Provides additional emulsification to help disperse oil and organic contaminants, making them easier to wash away.

[0019] Dodecyl polyoxyethylene ether: This is a very effective emulsifier and surfactant that can break the oil-water interface and enhance the cleaning fluid's removal effect on oily pollutants.

[0020] These nonionic surfactants are particularly suitable for use with sensitive basalt fibers due to their mild and nonionic properties (no charge) and will not damage the fibers themselves through chemical reactions:

[0021] Good compatibility: The above nonionic surfactants have good compatibility and will not cause damage or chemical deterioration of the fibers.

[0022] Low foaming and easy rinsing: These surfactants produce less foam and are easy to rinse, thus avoiding leaving residues on the fibers, which is particularly important for subsequent fiber processing.

[0023] Environmental safety and biodegradability: Selecting environmentally friendly nonionic surfactants can help reduce the impact of the production process on the environment.

[0024] Control of cleaning temperature (50-60°C): Temperature plays an important role in improving cleaning efficiency. When controlled within the range of 50-60°C, heat energy helps reduce the surface tension of surfactants and pollutants, increases the solubility of pollutants, and thus improves the cleaning effect.

[0025] The materials and conditions used are designed to ensure that the basalt fibers have good chemical reactivity and physical properties in subsequent steps. This is achieved by removing surface contamination and optimizing the surface state. These treatments provide the fibers with optimal surface conditions for subsequent chemical modification and physical processing.

[0026] S2 Fiber surface optimization treatment: Metal impurity removal treatment: The cleaned basalt fiber is immersed in ethylenediaminetetraacetic acid solution for soaking. After the soaking operation is completed, it is rinsed with deionized water until it is neutral to obtain purified basalt fiber; the concentration of ethylenediaminetetraacetic acid solution is 0.3%-0.5%;

[0027] Active strengthening: immersing the purified basalt fiber in a sodium hydroxide mixed solution for soaking. After the soaking operation is completed, it is rinsed with deionized water until it is neutral to obtain pretreated basalt fiber filaments;

[0028] The sodium hydroxide mixed solution contains an auxiliary agent, which is one of polysorbate-20, polyvinyl pyrrolidone and dodecyl polyoxyethylene ether; the concentration requirements of the auxiliary agent are as follows: the concentration of polysorbate-20 is 0.08%-0.2%; the concentration of dodecyl polyoxyethylene ether is 0.1%-0.2%;

[0029] Considering the chemical composition and production process of basalt fiber precursor, the reasons for using 0.3%-0.5% ethylenediaminetetraacetic acid solution (EDTA) are as follows: Removal of metal ion contamination: The production process of basalt fiber may introduce or expose various metal ions, such as iron, calcium, magnesium, etc. These metal ions will affect the quality and performance of the fiber. EDTA, as a chelating agent, can form stable chelates with these metal ions, release them from the fiber surface and dissolve them in water, thereby being removed; the fiber after removing metal impurities has a cleaner surface, which is very beneficial for subsequent chemical treatment and coating applications, and enhances the mechanical properties and chemical resistance of the fiber; appropriate concentration: using 0.3%-0.5% EDTA concentration can ensure sufficient chelation ability while avoiding chemical attacks on the fiber. This concentration balances efficiency and mildness, which can effectively remove metal impurities and protect the fiber structure from being destroyed.

[0030] The purpose of active strengthening treatment is as follows: destroy the fiber surface structure: in an alkaline environment, Na ions can replace metal ions (such as Ca) in the silicon-oxygen structure of the fiber surface, thereby increasing the surface roughness; increasing the roughness of the fiber surface by alkali treatment has several significant benefits, which play a key role in the preparation method of the entire basalt fiber winding tape roll, especially in improving the overall performance; increase the possibility of chemical modification: the rough surface provides more active sites for subsequent chemical modification; enhance mechanical bonding: the increase in the roughness of the fiber surface can significantly improve the mechanical interlocking between the fiber and the resin in the subsequent steps. The rough surface provides more microscopic anchor points, and the resin can form a better mechanical interlocking on these irregular surfaces, thereby improving the shear strength and tensile strength of the composite material. Improve overall performance: The rough surface structure allows the resin to penetrate deeper into the tiny spaces between the fibers, thereby increasing the contact area and bonding strength between the fiber and the resin. This close bonding helps to transfer stress more effectively and increase the impact resistance and fatigue resistance of the material.

[0031] Introduction of hydroxyl groups: Alkaline solvent sodium hydroxide can react with the siloxy groups (Si-O-Si) on the fiber surface. This reaction first involves the breaking of the siloxy bond in an alkaline environment, and then the new hydroxyl group (-OH) combines with the exposed silicon atom to form a hydroxyl-siloxy (Si-OH) structure. This hydroxylation process greatly increases the polarity of the fiber surface. The hydroxyl group (-OH) introduced on the basalt fiber surface reacts chemically with the trimethoxysilane group in the coupling agent γ-methacryloxypropyltrimethoxysilane (γ-MPS) in the subsequent step to form a stable chemical bond. The formation of this chemical bond helps the coupling agent to be better fixed on the fiber surface;

[0032] Reduce contact angle and improve wettability: The hydroxyl groups introduced by alkali treatment also lead to a significant decrease in the contact angle of the fiber surface, which means that the wettability of the fiber surface is improved. The lower contact angle helps the treatment agent in the subsequent steps to be more evenly distributed on the fiber surface, thereby improving the treatment effect and product quality.

[0033] Polysorbate 20: Function: Polysorbate 20 is a nonionic surfactant that can reduce the surface tension of water and increase the hydrophilicity of the basalt fiber surface. It can help chemicals to be more evenly distributed on the fiber surface and improve the treatment effect;

[0034] Concentration selection (0.08%-0.2%): This concentration range is sufficient to provide effective surfactant without being excessive. Too high a concentration may cause the fiber surface to be too sticky;

[0035] Laureth-12: Function: As a surfactant, it can enhance the interfacial interaction between the fiber and the alkaline mixed solution, thereby improving the processing efficiency and uniformity. It also helps the solution penetrate deeper into the fiber.

[0036] Concentration selection (0.1%-0.2%): This range ensures sufficient surface active action without causing excessive absorption of chemicals by the fiber, which would affect its physical and chemical stability.

[0037] S3: preparing a coupling agent solution: ethanol and deionized water are mixed evenly, and the mixture is used as a solvent. The coupling agent is added to the solvent and stirred evenly, and then an acidic catalyst is added, and the stirring is continued until the mixture is evenly mixed to obtain a coupling agent solution.

[0038] The coupling agent is γ-methacryloxypropyltrimethoxysilane;

[0039] The acid catalyst is hydrochloric acid;

[0040] γ-Methacryloxypropyltrimethoxysilane was selected as the coupling agent due to its unique chemical structure and the binding force it provides. The main reasons are as follows:

[0041] Chemical structure and reactivity: γ-methacryloxypropyltrimethoxysilane (usually referred to as γ-MPS) has two main reactive groups: trimethoxysilane group (-Si(OCH3)3): under the action of water, it reacts with the hydroxyl group (-OH) on the surface of basalt fiber to form a stable silicon oxygen bond (Si-O-Si). This bond is very strong and can effectively improve the bonding force between the fiber and the coupling agent. Hydrochloric acid is used as a catalyst in this process to accelerate the hydrolysis reaction between the methoxy group in the coupling agent and the hydroxyl group on the surface of basalt fiber. The addition of hydrochloric acid accelerates the hydrolysis rate of the methoxy group of silane to form more active silane hydroxyl groups, which can react with the hydroxyl groups on the fiber surface more quickly to form chemical bonds.

[0042] Acryloyloxy (with active double bonds): This group can react with the carboxyl group in the carboxylated nano-silica in the following steps by covalent bonding, and the carboxylated nano-silica is firmly anchored on the fiber surface. The advantages of introducing carboxylated nano-silica are as follows: Enhanced mechanical properties: By adding carboxylated nano-silica, a uniform nanoparticle coating can be formed on the fiber surface, which helps to increase the rigidity and tensile strength of the material. The high specific surface area and active sites of the nanoparticles can effectively bear and disperse stress, thereby reducing the local stress concentration of the material when subjected to external forces, and improving its fracture resistance and impact resistance. Improved thermal stability: The introduction of carboxylated nano-silica can also improve the thermal stability of the material. These nanoparticles can withstand high temperatures without significant structural changes, thereby protecting the performance of the fiber in high temperature environments and extending its service life. Increased surface roughness: The rough surface increases the mechanical interlocking between the fiber and the resin, thereby increasing the interfacial shear strength of the composite material. Carboxylated nano-silica can increase the roughness of the fiber surface at a microscopic level, improve its mechanical bite with the resin, and thus improve the overall performance of the composite material. Improve chemical stability: Carboxylated nano-silica can provide better chemical corrosion resistance in materials due to its stable chemical structure.

[0043] S4 coupling agent-mediated surface modification: the pretreated basalt fiber is immersed in deionized water for wetting, and the wetted basalt fiber is transferred to a solution containing a coupling agent for immersion. After the immersion, the excess solution on the surface is removed by blowing, and then a heat treatment is performed. After the heat treatment, the initial modified basalt fiber is obtained.

[0044] The main purpose of heat treatment is to ensure that the reaction between the coupling agent and the surface of the basalt fiber is complete, thereby forming a stable and uniform chemical bond structure. The advantages are as follows: Improve the completeness of the reaction: Heat treatment not only accelerates the reaction of individual silane groups, but also helps the uniform reaction of the entire treated surface. This ensures that the entire fiber surface is uniformly modified, avoiding local unreacted areas, which is crucial to the overall performance of the material; Stabilize the chemical structure: Through heat treatment, it helps to maintain long-term environmental stability and durability;

[0045] S5 nanoparticle grafting: the initial modified basalt fiber is immersed in the grafting mixed solution for soaking. After the soaking operation is completed, the excess solution on the surface is removed by blowing, and then a heat treatment operation is performed. After the heat treatment operation is completed, the modified basalt fiber is obtained;

[0046] The grafting mixture is composed of carboxylated nano-silica, ethanol, deionized water, polysorbate-80 and ammonium persulfate. The weight ratio of carboxylated nano-silica: ethanol: deionized water: polysorbate-80: ammonium persulfate is 3-4: 40-50: 35-40: 0.8-1.2: 0.3-0.4;

[0047] The above ratios are selected to ensure effective grafting reaction and optimize the surface properties of the fiber. The selection and ratio of each component are targeted to address specific needs. The following are the specific reasons:

[0048] Carboxylated nanosilica (3-4): As the main grafting component, carboxylated nanosilica forms chemical bonds with the groups on the surface of basalt fibers through the carboxyl groups on its surface. It is very important to control its concentration. High concentration can increase the grafting rate, but it may also cause particle aggregation. The aggregation phenomenon will affect the dispersion of nanoparticles and lead to the formation of an uneven coating on the fiber surface, thereby reducing the consistency and predictability of the material's performance. Aggregation may also block the pores inside the fiber, affecting its intrinsic properties such as air permeability and hygroscopicity. Controlling the concentration at 3-4% is a balancing strategy aimed at optimizing the grafting effect and avoiding potential negative effects.

[0049] Ethanol (40-50) and deionized water (35-40): These two solvents are used to disperse and stabilize the nanoparticles and as a medium for the grafting reaction. The ratio of ethanol to water is adjusted to ensure the appropriate viscosity of the solution and reaction conditions so that the grafting reaction can proceed evenly and effectively.

[0050] The main function of polysorbate-80 is to help the nanoparticles disperse evenly in the solution and prevent them from aggregating during the grafting process. The ratio of 0.8-1.2 is enough to form a stable dispersion system, but it does not affect the viscosity of the solution too much; the selection and ratio of polysorbate-80 also need to consider its compatibility with other components, such as ethanol, deionized water, and nano-silica. The appropriate ratio can ensure that all components can work together effectively when mixed without adverse effects caused by interactions. The 0.8-1.2 ratio of polysorbate-80 is a balance point reached after many considerations.

[0051] The role of ammonium persulfate in this type of reaction is to decompose and generate free radicals, which will initiate and promote the grafting reaction between nanoparticles and fiber surfaces. Within the ratio range of 0.3-0.4, ammonium persulfate can generate enough free radicals to maintain the continuation and integrity of the reaction.

[0052] S6 basalt fiber ribbon forming: S6.1 Fiber pre-finishing: Use fiber arrangement equipment to arrange the modified basalt fiber according to the preset density and direction to form a uniform and continuous fiber bundle;

[0053] S6.2 Strip forming process: Use a strip forming device to form the fiber bundle into a strip body with a preset width and thickness to obtain an initial black fiber winding strip;

[0054] S7: prepare resin liquid: add vinyl ester resin into a container with stirring function, then add methyl ethyl ketone as solvent into the container, start the stirring equipment to perform the first stirring operation, and obtain a basic resin solution; add leveling agent and curing agent into the basic resin solution, and perform the second stirring operation until it is completely blended; then add antioxidant, perform the third stirring operation, and stir until there are no visible particles in the mixed liquid; finally, add antistatic agent into the resin liquid, perform the fourth stirring operation, and stir until it is completely mixed; after the stirring is completed, let it stand for a period of time to allow bubbles to float up and burst naturally, and finally obtain performance-enhanced resin liquid;

[0055] According to the weight ratio, vinyl ester resin: methyl ethyl ketone: leveling agent: antioxidant: antistatic agent: curing agent is 95-98:15-17:0.8-1:0.45-0.5:0.18-0.2:0.7-1;

[0056] The leveling agent is polydimethylsiloxane, the antioxidant is tetrakis (2,4-di-tert-butylphenol)-4,4-biphenyl diphosphite; the antistatic agent is a quaternary ammonium salt antistatic agent; the curing agent is benzoyl peroxide;

[0057] The reasons for configuring the above resin solution are as follows:

[0058] 1. Performance characteristics of vinyl ester resin: Vinyl ester resin has good chemical stability and mechanical properties, can withstand complex environmental conditions, and is particularly suitable for applications that require long-term durability, such as pipe linings. Vinyl ester resin also has high strength, chemical corrosion resistance and good process performance, while avoiding the shortcomings of epoxy resin such as high viscosity, difficult processing and high cost. Its corrosion resistance and alkali resistance are comparable to those of epoxy resin, while its oxidation resistance and acid resistance are comparable to those of bisphenol unsaturated polyester resin. Vinyl ester resin also has excellent curing performance and molding speed. In addition, it also has good high elongation and glass fiber impregnation, which is suitable for large-scale on-site winding, pultrusion processes, etc. After curing, vinyl ester resin has good insulation properties. The withstand voltage of a pure resin 1mm casting plate reaches 14-18kV, the volume inherent resistance is generally ≥1015Ω.cm, and the surface inherent resistance value is generally ≥1012Ω. These data show that vinyl ester resin also performs well in electrical insulation. ‌

[0059] 2. Compatibility of vinyl ester resin with other ingredients:

[0060] Vinyl ester resin has good compatibility with other additives (such as methyl ethyl ketone, leveling agent, antioxidant, antistatic agent and curing agent). This makes it possible to adjust the fluidity, curing time and final performance of the resin by adding different auxiliary ingredients in the process of preparing performance-enhanced resin liquid to meet application requirements.

[0061] 3. Reason for the proportion of vinyl ester resin: In the ratio, the high proportion of vinyl ester resin (95-98) ensures that the structure of the final product is mainly composed of resin, providing sufficient matrix support to maintain the fiber reinforcement effect and the structural integrity of the overall material. The higher resin content helps to optimize the mechanical properties and chemical stability of the black fiber winding tape, so that it can show higher performance in composite pipe applications.

[0062] 4. Functions of other additives: Methyl ethyl ketone (15-17) acts as a solvent to help vinyl ester resin maintain appropriate viscosity during processing, facilitating coating and molding.

[0063] Leveling agent (0.8-1) is used to improve the surface quality of the coating and reduce bubbles and unevenness that may occur during the coating process.

[0064] Antioxidants and antistatic agents (0.45-0.5 and 0.18-0.2) are used to enhance the durability of materials and reduce static electricity accumulation, improving safety and long-term stability. In gas transportation, for example, hydrogen is a highly flammable gas, and its safety during transportation is crucial. Static electricity accumulation can cause hydrogen to ignite, leading to serious safety accidents. Quaternary ammonium antistatic agents effectively reduce the generation and accumulation of static electricity and reduce the risk of ignition by forming a conductive layer on the surface of the material. Hydrogen transportation often involves different temperature and pressure conditions, which may exacerbate static electricity problems. Quaternary ammonium antistatic agents can provide continuous antistatic protection under a wide range of environmental conditions, ensuring that their effectiveness is maintained throughout the transportation process. Ammonium antistatic agents have good compatibility with other materials in the resin liquid and can be effectively dispersed in the coating without changing the chemical properties of the substrate. This makes them easy to apply during the manufacturing process and can provide the required antistatic effect without affecting other mechanical properties of the material.

[0065] Types of quaternary ammonium antistatic agents include: benzalkonium quaternary ammonium salts; fatty acid quaternary ammonium salts, such as trimethylammonium stearate; di-long chain quaternary ammonium salts, such as methylammonium distearate, which provide a long-lasting antistatic effect and enhance the handling characteristics of the material.

[0066] The curing agent (0.7-1) is used to promote the cross-linking reaction of the vinyl ester resin and improve the mechanical strength and chemical cross-linking density of the material. Benzoyl peroxide decomposes to produce free radicals, which can initiate the double bond open chain polymerization reaction in the resin to form a three-dimensional network structure; but the curing reaction requires a certain temperature and time to complete. The coating and pre-curing treatment mentioned in step S8 ensures that the curing reaction of the resin proceeds gradually during the coating process rather than occurring immediately;

[0067] There is another key point that has not been mentioned before, that is, the surface of the initial black fiber winding tape prepared in step S6 will contain the acryloyloxy group of the coupling agent that has not completely reacted with the carboxylated nano-silica, which can copolymerize with the vinyl group (also an unsaturated double bond) in the vinyl ester resin. This reaction is carried out through a free radical mechanism in the presence of a curing agent. The acryloyloxy group of the coupling agent can undergo a cross-linking reaction with the double bonds in the resin to form a more complex network structure. This cross-linking helps to improve the structural strength and chemical resistance of the material; because γ-MPS can react chemically with the vinyl ester resin, it helps to improve the interfacial bonding between the resin and the fiber. Through the formation of chemical bonds, the coupling agent can more effectively combine the fiber and the resin, enhancing the mechanical properties and durability of the material; it not only improves the bonding strength of the material, but also improves the interface compatibility and reduces internal defects;

[0068] S8 coating and rolling: coating: the coating machine is used to evenly coat the performance enhancing resin liquid on the preheated initial black fiber winding tape to obtain the coated black fiber winding tape; the coating machine is equipped with a coating roller to ensure the uniformity of the coating and precise thickness control; the coating machine is equipped with a heating device for preheating the initial black fiber winding tape;

[0069] Post-coating treatment: The coated black fiber winding tape is sent into the pre-curing tunnel for pre-curing treatment. The temperature of the pre-curing tunnel is controlled at 60-80°C.

[0070] Roll making: Use a winding machine to roll the pre-cured coated black fiber winding tape into a roll to obtain a black fiber winding tape roll.

[0071] The reasons for choosing 60-80°C are as follows: Resin curing requirements: In the case of vinyl ester resins, the curing process of the resin usually requires heat energy to activate the curing agent (benzoyl peroxide) to initiate a chemical reaction. The temperature range of 60-80°C is suitable for activating such peroxide curing agents without over-accelerating the reaction, resulting in coating defects such as uneven curing or premature curing;

[0072] Coating quality control: A pre-curing temperature of 60-80°C helps maintain the fluidity of the coating, allowing the coating machine to distribute the resin liquid more evenly. Too low a temperature will increase the viscosity of the resin, making it difficult to form a uniform coating; too high a temperature will cause the resin to cure prematurely or the volatile components to evaporate too quickly, affecting the overall quality and performance of the coating. Keep the coated black fiber winding tape sticky enough to increase the bonding strength between layers during later winding.

[0073] Preferably, in step S1, the parameter requirements of the basalt fiber precursor are as follows: silicon dioxide content is 52-54%; aluminum oxide content is 12-15%; calcium oxide content is 9-11%; magnesium oxide content is 9-10%, and the total content of ferrous oxide and ferric oxide is 12-13%; titanium dioxide content is 1.5-2%; the total content of sodium oxide and potassium oxide is not higher than 1%; diameter is 10-12 microns; elongation at break is not less than 3.5%.

[0074] The above parameter requirements are to enable basalt fiber to show the best performance in specific applications (such as winding composite pipe lining). For example, silica is a key component that affects the heat resistance and mechanical properties of basalt fiber. In the range of 52-54%, silica helps to form a good fiber structure, and alumina enhances the heat resistance, corrosion resistance and mechanical strength of the fiber. Alumina, as a component of basalt fiber, can improve the crystallinity of the fiber at a ratio of 12-15%, thereby enhancing its service life and functionality; the diameter is 10-12 microns. This diameter range ensures that the fiber has sufficient flexibility to adapt to various molding and application requirements, while maintaining sufficient mechanical strength and durability; the elongation at break is not less than 3.5%, and it has good ductility, so that it can effectively withstand loads and stresses in composite materials and improve the stability and durability of the overall structure.

[0075] The specific parameter requirements for basalt fiber precursor are based on ensuring the performance optimization of the fiber in production and final use. Each parameter is set to ensure that the fiber can achieve the expected physical and chemical properties in the application.

[0076] Preferably, in step S2, in the metal impurity removal treatment step, the temperature of the EDTA solution is 35-45° C.; the immersion time is 20-30 minutes;

[0077] The pH value of the sodium hydroxide mixed solution is 11-13;

[0078] After the fiber surface optimization treatment, the contact angle of the pretreated basalt fiber is required to be less than 30°.

[0079] After actual verification, the active strengthening operation time is 15-20 minutes. If the contact angle fails to meet the requirement of less than 30°, the treatment time can be appropriately extended, but the total time should not exceed 30 minutes to avoid damaging the fiber.

[0080] EDTA solution temperature is 35-45°C: Ethylenediaminetetraacetic acid (EDTA) is a powerful chelating agent used to remove metal impurities from fibers. In the temperature range of 35-45°C, EDTA has a high chelating activity and can effectively react with metal ions in fibers while avoiding excessively high temperatures that may cause fiber damage or degradation. This temperature range is designed to balance chelation efficiency and physical stability of the fiber.

[0081] Immersion time is 20-30 minutes: This time range is based on the need for sufficient time for EDTA to fully react with metal impurities, while taking into account that too long a treatment time may cause unnecessary chemical or physical damage to the fiber. 20-30 minutes can be considered a compromise to ensure that impurities are effectively removed without affecting the quality of the fiber itself.

[0082] The pH value of the alkaline mixed solution is 11-13: The alkaline environment helps to open the surface structure of the fiber and increase the active sites of the fiber, which is extremely important for subsequent chemical modification or grafting reactions. The strong alkaline environment with a pH value of 11-13 can effectively promote the activation of the fiber surface, but it must also be controlled within a safe range to prevent excessive corrosion or weakening of the fiber. This pH range can ensure that the fiber surface is fully activated without damaging its mechanical properties.

[0083] The contact angle of the pretreated basalt fiber is required to be less than 30°: The contact angle is an important indicator used in surface science to measure the hydrophilicity or hydrophobicity of the material surface. A low contact angle of less than 30° indicates that the fiber surface has a high hydrophilicity, which is a result of significant improvement through surface treatment. A highly hydrophilic surface is more conducive to subsequent chemical modifications, such as the application of coupling agents or the grafting of nanoparticles, because such a surface can better interact with the treatment liquid and improve the efficiency and uniformity of the chemical reaction. The drop method is used when measuring the contact angle. The specific steps are as follows: 1. Prepare experimental materials and equipment: High-precision dropper: used to accurately control the size and shape of the droplet. High-resolution camera: used to capture the moment when the droplet contacts the fiber.

[0084] Contact angle measurement software: such as ImageJ or dedicated contact angle analysis software. Laboratory environment control equipment: ensure a constant temperature and humidity environment.

[0085] 2. Fixation and leveling of fibers: Fixation: Use appropriate clamps to fix the pretreated basalt fiber on the observation platform to keep the fiber stable and level.

[0086] Inspection: Check the flatness and cleanliness of the fibers using a microscope or magnifying glass.

[0087] 3. Dropping operation: Drop placement: Use a dropper to carefully place an appropriate amount of water drop (or other test liquid) on the pretreated basalt fiber. The drop size should be moderate to avoid deformation of the drop due to gravity.

[0088] 4. Filming and recording: Camera settings: Adjust the camera to ensure that the contact point between the droplet and the fiber can be clearly captured.

[0089] Photographing: Take multiple photos immediately after placing the droplet to capture the initial contact angle of the droplet.

[0090] 5. Image analysis: Import the image: Import the image into the contact angle measurement software. Angle measurement: Use the software tool to calibrate and measure the contact angle between the droplet edge and the fiber.

[0091] 6. Data recording and analysis: Repeated measurements: To improve the reliability of the data, repeat the measurement at least three times and record all the data.

[0092] Average calculation: Calculate the average of multiple contact angle measurements to get more accurate results.

[0093] 7. Evaluation and Report Preparation: Evaluation: Analyze the contact angle data to evaluate the hydrophilicity or hydrophobicity of the fiber surface. Report: Write a lab report that details the experimental conditions, methods used, data obtained, and final analysis results.

[0094] Preferably, in step S3, the pH value of the coupling agent solution is 4-5; in the coupling agent solution, the concentration of the coupling agent is 3%-5%; in the solvent, the weight ratio of ethanol: water is 7:2-3.

[0095] pH value is 4-5: coupling agent activity: coupling agent γ-methacryloxypropyltrimethoxysilane is an organic silicon compound, and the hydrolysis and condensation reaction of its silane group is sensitive to pH value. In an acidic environment (pH 4-5), the silane group can be more effectively hydrolyzed and form silanol, which helps it to further react with the hydroxyl group on the surface of basalt fiber to form a stable chemical bond.

[0096] Avoid excessive hydrolysis: Too low a pH value (too acidic) will cause excessive hydrolysis of the silane group to form aggregates, which will reduce its effective reactivity with the fiber. Therefore, a moderately acidic environment helps control the degree of hydrolysis and avoid a decrease in the effectiveness of the coupling agent.

[0097] The coupling agent concentration is 3%-5%: Sufficient surface coverage: This concentration range ensures that there are enough coupling agent molecules in the coupling agent solution to cover and react with the surface of the basalt fiber, which helps to form a continuous chemical modification layer. Avoid oversaturation and aggregation: Too high a concentration may cause the coupling agent to aggregate on the fiber surface, forming an uneven coverage layer, which may affect the mechanical properties of the fiber and the overall quality of the composite material.

[0098] Solvent ratio ethanol: water is 7:2-3: Solvent efficiency and reaction conditions: This ratio of ethanol to water is designed to optimize the volatility of the solvent and the stability of the reaction environment. As the main solvent, ethanol can effectively dissolve the coupling agent and accelerate the drying process after the reaction. The role of water: Water is not only part of the solvent system, but also plays a key role in the hydrolysis of the coupling agent. The right amount of water helps promote the hydrolysis reaction of the coupling agent to generate more active silanol groups. This ratio ensures that there is enough water to participate in the reaction while avoiding excessive reaction rate or poor reaction control due to excessive water.

[0099] Comprehensive effect: The setting of these parameters is not only related to the efficiency and quality of the chemical reaction, but also directly affects the application performance of the final product. By optimizing these parameters, better interfacial adhesion can be achieved and the mechanical properties and durability of the composite material can be improved. In addition, controlling these conditions also helps to improve the predictability and repeatability of the production process, thereby ensuring the consistency and reliability of product quality. Such parameter settings are determined on the basis of experiments and practice, and aim to maximize product performance by precisely controlling the chemical and physical conditions in the production process.

[0100] Preferably, in step S4, in the air blowing method, the specific requirements are as follows: distance height: 5-10 cm; angle: nozzle 30-45°; nozzle distribution: multiple nozzles are arranged horizontally and evenly distributed above or on both sides of the fiber;

[0101] The requirements for the heat treatment operation are as follows: at the beginning, heat from room temperature to 100-120°C, and control the heating rate at 2-5°C / min. Use thermogravimetric analysis technology to continuously monitor the heat treatment process. When the mass loss curve tends to be stable and there is no further mass loss, end the heat treatment and reduce the temperature to room temperature. The cooling rate is controlled at 2-5°C / min.

[0102] Reasons for setting parameters of the air blowing method: Distance height (5-10 cm): This height range is to ensure that the air blowing can effectively remove excess coupling agent solution on the surface. If the distance is too far, the effect may not be good.

[0103] Angle (30-45°): The angle of the nozzle is set to maximize coverage and evenly remove surface liquid. This angle range helps achieve uniform liquid removal and avoids localized accumulation or uneven drying.

[0104] Nozzle distribution (multiple nozzles arranged horizontally, evenly distributed above or on both sides of the fiber): This layout helps to achieve uniform treatment of the fiber surface, ensuring that every part of the fiber is properly treated. Even distribution helps to improve product consistency and quality.

[0105] Requirements for heat treatment: Selecting a temperature range of 100-120°C can effectively promote the chemical reaction between the coupling agent and the surface of the basalt fiber to form a reinforced interface; Heating rate (2-5°C / min): This heating rate is to control the thermal stress during the heat treatment process to prevent the fiber from being damaged or deformed due to a rapid temperature rise. A gentle heating rate helps maintain the structural stability and chemical properties of the fiber. Cooling rate (2-5°C / min): Controlling the cooling rate is also important. Slow cooling helps avoid thermal stress or fiber structure damage caused by rapid temperature changes.

[0106] Preferably, in step S5, the requirements for the heat treatment operation are as follows: at the beginning, heating is performed from room temperature to 110-120°C, the heating rate is controlled at 2-3°C / min, and the heat treatment process is continuously monitored using thermogravimetric analysis technology. When the mass loss curve tends to be stable and there is no further mass loss, the heat treatment is terminated and the temperature is reduced to room temperature, and the cooling rate is controlled at 2-3°C / min.

[0107] Thermogravimetric analysis (TGA) is a technique used to monitor the mass change of a sample during heating, which is critical to understanding the thermal stability and thermal degradation behavior of a material. This monitoring allows for real-time evaluation of the thermal stability and degree of curing of coupling agents, grafting agents, and other treatment chemicals.

[0108] When the mass loss curve tends to be stable, it indicates that the main thermal reaction has been completed and reached equilibrium. At this time, further heating will not bring additional chemical or physical changes, so the heating can be terminated.

[0109] Preferably, in step S6, in the fiber pre-finishing step, the fiber arrangement device is specifically an automated fiber arrangement machine; arrangement density: 0.1-0.5 mm; arrangement direction: parallel to the forward direction of the belt-shaped forming device to reduce the crossing and entanglement between fibers; speed control: the arrangement speed is synchronized with the forming speed to ensure the continuous supply and uniform distribution of fibers;

[0110] In the strip forming processing step, the strip forming equipment is specifically a strip forming calender with a heating function, the heating temperature is 40-50°C; the calendering speed is 1-3m / min.

[0111] Heating temperature: 40-50°C: Promote bonding: The main purpose is to slightly heat the fiber to improve the bonding effect between the fiber and the resin. At this temperature, the fluidity of the resin may increase slightly, but it will not flow or solidify excessively, which helps to maintain good control during the calendering process. Improve processability: This range of temperature can improve the flexibility and processability of the strip material, making the material easier to form and manipulate during calendering, while avoiding the stiffness of the material caused by too low a temperature or softening and deformation caused by too high a temperature.

[0112] Calendering speed: 1-3m / min: Quality control: This speed range ensures stable processing of fibers and resins on the production line, avoiding the risks of too fast, such as fiber breakage, entanglement or uneven resin distribution. Accurate forming: The appropriate calendering speed helps ensure that the calender can evenly press the fiber into a ribbon while maintaining the preset thickness and width specifications. Too fast speed may cause uneven forming, while too slow speed may reduce production efficiency.

[0113] Preferably, in step S7, in the first stirring operation, the stirring speed is 100-300 RPM; in the second stirring operation, the stirring speed is 200-400 RPM; in the third stirring operation, the stirring speed is 150-350 RPM; in the fourth stirring operation, the stirring speed is 100-300 RPM;

[0114] In step S8, the pre-curing treatment time is 10-15 minutes.

[0115] First stirring operation (100-300 RPM): Purpose: Mix the vinyl ester resin and methyl ethyl ketone to form a base resin solution. The purpose of this step is to ensure that the resin and solvent are fully mixed and there are no large pieces of undissolved resin.

[0116] The stirring speed is low: to avoid introducing too much air, which will lead to excessive bubble generation, while ensuring uniform dissolution of the resin and avoiding excessive shear force that will damage the resin structure.

[0117] Second stirring operation (200-400 RPM): Purpose: Add leveling agent and curing agent for deeper mixing, higher stirring speed: In this step, a higher stirring speed is required to ensure that the added curing agent and leveling agent can be quickly and evenly distributed in the resin.

[0118] Third stirring operation (150-350 RPM): Purpose: Add antioxidants and continue to ensure mixing uniformity. Medium stirring speed: At this time, the stirring speed must ensure uniform distribution of antioxidants and avoid introducing too many bubbles, because the addition of antioxidants is more sensitive and requires fine control.

[0119] Fourth stirring operation (100-300 RPM): Purpose: Add antistatic agent and complete the final mixing. Stirring speed is low: The final stirring is mainly to make all ingredients thoroughly blended and there are no visible particles in the liquid. The stirring speed returns to a lower range to avoid destroying the resin structure that has been formed and reduce bubbles.

[0120] An application of a black fiber winding tape roll, a black fiber winding tape roll prepared by the preparation method of the black fiber winding tape roll; the black fiber winding tape roll is unrolled, and is bonded to the circumferential outer wall of the inner lining layer of a composite pipe by winding, heating and bonding, as a reinforcement layer; the protective layer of the composite pipe is fixed to the outer periphery of the reinforcement layer by extrusion molding; the inner lining layer and the protective layer are both made of thermoplastic resin material; the composite pipe as a whole adopts a fully fused solid wall structure; the specific application steps are as follows:

[0121] A1: Apply adhesive: Before winding, apply a layer of adhesive on the outer wall of the inner lining layer;

[0122] A2 winding: Use the black fiber winding tape to wrap around the circumferential outer wall of the inner liner coated with adhesive; the overlap during winding accounts for 20%-50% of the bandwidth;

[0123] A3 curing treatment: After winding is completed, curing treatment is carried out, and the curing temperature is 100-140°C. The set curing temperature range of 100-140°C can effectively promote the cross-linking of materials such as vinyl resins, and obtain a black fiber winding tape with good mechanical properties and high chemical stability. This temperature range helps to optimize the strength and durability of the product, so that it can withstand longer-term use and external environmental challenges in practical applications; this range of curing temperatures helps to reduce defects that may occur during the preparation process, such as bubble formation, uneven curing, etc. Higher curing temperatures help to expel bubbles in the mixture faster, while ensuring the uniformity and continuity of the resin mixture, and avoiding uncured or partially cured areas that affect the overall performance.

[0124] In step A1, it is critical to select the right adhesive to ensure excellent adhesion and chemical compatibility between the wrapping tape and the inner liner; Adhesive selection principles: When selecting an adhesive, the following factors should be considered: Chemical compatibility: The adhesive should be compatible with the pipeline material and basalt fiber to avoid material degradation caused by chemical reactions. Temperature stability: The adhesive needs to be able to withstand the highest curing temperature during the application process without degradation. Mechanical properties: The adhesive should have sufficient strength and elasticity to maintain the structural integrity of the pipeline and adapt to various mechanical stresses.

[0125] Here are a few types of adhesives and why to choose them:

[0126] 1. Epoxy resin adhesive: Epoxy resins have excellent mechanical properties and bonding strength, and can withstand high loads and chemical erosion. They perform well at high temperatures and can match the thermal properties of basalt fiber. Epoxy resins can be accelerated by heating during the curing process, which is compatible with the curing temperature of 100-140°C of basalt fiber winding tape.

[0127] 2. Polyurethane adhesive: Polyurethane adhesive provides good flexibility and fatigue resistance, helping to cope with possible thermal expansion and contraction of the liner.

[0128] They generally have good water and chemical resistance and are suitable for pipe linings that may be exposed to wet environments or chemicals.

[0129] 3. Vinyl ester adhesive: Vinyl ester adhesives provide extremely high chemical resistance and temperature stability after hardening, which matches the expected use environment of the Xuan Fiber winding tape roll. Their curing characteristics can be adjusted by heating, which is very suitable for use in high temperature curing processes.

[0130] When winding in step A2, different winding angles are required according to different construction purposes. The winding angle refers to the inclination angle of the black fiber winding tape relative to the axis of the pipeline. This parameter has an important influence on the mechanical properties and anti-permeability of the pipeline; ±45° angle: suitable for applications requiring high torsional stiffness and good lateral strength, which helps to enhance the overall structural stability of the pipeline; ±55° to ±70° angle: provides a better balance of axial and radial strength to cope with the high-pressure characteristics of the gas and prevent penetration; ±85° angle: mainly used to improve the axial strength of the pipeline, suitable for long-distance transportation and high-pressure applications; When describing the winding angle, "±" is usually used to indicate that the fiber winding direction can be clockwise or counterclockwise. For example, ±45° means that the fiber can be wound clockwise along a 45-degree angle, or it can be wound counterclockwise along a 45-degree angle. This usage is mainly to illustrate that the fiber can be wound in two symmetrical directions to achieve design balance and symmetry.

[0131] Compared with the prior art, the present invention has the following beneficial effects:

[0132] 1. Improve overall performance: Introduce nano-silica: Due to its extremely high surface area to volume ratio, nano-silica can form a more dense and uniform filling in the microstructure of the fiber, which helps to increase the overall strength and toughness of the basalt fiber. When nano-silica is combined with the fiber matrix, it can significantly improve the tensile strength, compressive strength and impact toughness of the composite material; the hardness and wear resistance of nano-silica also help to improve the surface wear resistance of the fiber and extend the service life of the material. Nano-silica has very good chemical inertness and can enhance the stability of fiber materials in a variety of chemical environments; the addition of nano-silica can change the surface properties of the fiber, such as increasing the surface roughness and increasing the surface energy, which helps the bonding effect between the resin and the fiber, thereby improving the overall performance of the composite material; the composite effect of the resin: After the surface treatment of the basalt fiber, the vinyl ester resin is coated to increase the overall structural strength of the material. In addition, leveling agents, curing agents, antioxidants and antistatic agents are added to the resin mixture. These additives optimize the fluidity, curing time, oxidation resistance and electrical resistance of the resin, so that the final product shows better physical and chemical stability in practical applications.

[0133] 2. Deep surface cleaning treatment: The deep surface cleaning process uses non-ionic surfactants to clean the basalt fiber raw yarn, effectively removing surface pollutants and improving the purity and hydrophilicity of the fiber. This cleaning treatment not only protects the original physical properties of the fiber, but also provides a uniform and controllable surface for subsequent chemical treatment.

[0134] 3. Surface activity enhancement treatment: Through immersion in ethylenediaminetetraacetic acid solution and active enhancement treatment with sodium hydroxide mixed solution, metal impurities are effectively removed and the surface activity of the fiber is enhanced. These treatments improve the chemical reactivity of the fiber, provide more active sites for coupling agent treatment, and thus improve the functionalization level of the fiber.

[0135] 4. Precise control of coupling agent and heat treatment: Coupling agent-mediated surface modification achieves surface functionalization of basalt fiber through precisely controlled air blowing and subsequent heat treatment. This step not only removes excess coupling agent on the surface, but also strengthens the bonding between the coupling agent and the fiber surface through heat treatment.

[0136] In summary, the present invention significantly improves the comprehensive performance of the black fiber winding tape in composite pipe applications through a series of process optimizations and material modifications, and provides an effective improvement solution for existing material technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0137] Figure 1 Schematic diagram of the diameter cross section of the composite pipe in the second embodiment.

[0138] Figure 2It is a partial schematic diagram of the axial cross section of the composite pipe in the second embodiment.

[0139] Figure 3 It is a partial enlarged structural diagram of the reinforcement layer in the composite pipe in Example 2.

[0140] Figure 4 This is an enlarged view of the surface of the black fiber winding belt in Example 2.

[0141] 1. Inner lining layer; 2. Reinforcement layer; 3. Black fiber wrapping tape; 4. Protective layer. DETAILED DESCRIPTION

[0142] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments. Embodiment 1:

[0143] A method for preparing a black fiber winding tape roll, the method for preparing a black fiber winding tape roll comprising the following steps:

[0144] S1 Deep surface cleaning: Use a cleaning solution containing a non-ionic surfactant to clean the basalt fiber raw yarn, and the cleaning temperature is controlled at 50-60°C; after the cleaning operation is completed, rinse with deionized water to obtain cleaned basalt fiber yarn;

[0145] The nonionic surfactant is at least one of polyoxyethylene alcohol, polyethoxylated nonanoic acid ester and dodecyl polyoxyethylene ether;

[0146] The parameter requirements of basalt fiber precursor are as follows: silicon dioxide content is 52-54%; aluminum oxide content is 12-15%; calcium oxide content is 9-11%; magnesium oxide content is 9-10%, and the total content of ferrous oxide and ferric oxide is 12-13%; titanium dioxide content is 1.5-2%; the total content of sodium oxide and potassium oxide is not higher than 1%; diameter is 10-12 microns; tensile strength is not less than 3.5GPa, and elongation at break is not less than 3.5%.

[0147] S2 Fiber surface optimization treatment: Metal impurity removal treatment: The cleaned basalt fiber is immersed in ethylenediaminetetraacetic acid solution for soaking. After the soaking operation is completed, it is rinsed with deionized water until it is neutral to obtain purified basalt fiber; the concentration of ethylenediaminetetraacetic acid solution is 0.35%;

[0148] Active strengthening: immersing the purified basalt fiber in a sodium hydroxide mixed solution for soaking. After the soaking operation is completed, it is rinsed with deionized water until it is neutral to obtain pretreated basalt fiber filaments;

[0149] The sodium hydroxide mixed solution contains an auxiliary agent, which is one of polysorbate-20 and dodecyl polyoxyethylene ether; the concentration requirements of the auxiliary agent are as follows: the concentration of polysorbate-20 is 0.08%-0.2%; the concentration of dodecyl polyoxyethylene ether is 0.1%-0.2%;

[0150] In the metal impurity removal treatment step, the temperature of the EDTA solution is 39°C; the immersion time is 20-25 minutes;

[0151] The pH value of the sodium hydroxide mixed solution is 12;

[0152] After the fiber surface optimization treatment, the contact angle of the pretreated basalt fiber is required to be less than 30°;

[0153] S3: preparing a coupling agent solution: mixing ethanol and deionized water evenly, using the mixture as a solvent, adding a coupling agent to the solvent and stirring the mixture evenly, adding an acidic catalyst, and continuing to stir the mixture until the mixture is evenly mixed to obtain a coupling agent solution;

[0154] The coupling agent is γ-methacryloxypropyltrimethoxysilane;

[0155] The acid catalyst is hydrochloric acid;

[0156] The pH value of the coupling agent solution is 4; in the coupling agent solution, the concentration of the coupling agent is 3.5%; in the solvent, the weight ratio of ethanol to water is 7:2.5.

[0157] S4 coupling agent-mediated surface modification: the pretreated basalt fiber is immersed in deionized water for wetting, and the wetted basalt fiber is transferred to a solution containing a coupling agent for immersion. After the immersion, the excess solution on the surface is removed by blowing, and then a heat treatment is performed. After the heat treatment, the initial modified basalt fiber is obtained.

[0158] In the air blowing method, the specific requirements are as follows: distance height: 7 cm; angle: nozzle 45°; nozzle distribution: multiple nozzles are arranged horizontally and evenly distributed on both sides of the fiber;

[0159] The requirements for the heat treatment operation are as follows: at the beginning, heat from room temperature to 120°C, and the heating rate is controlled at 3°C / min. The heat treatment process is continuously monitored using thermogravimetric analysis technology. When the mass loss curve tends to be stable and there is no further mass loss, the heat treatment is terminated and the temperature is reduced to room temperature at a cooling rate of 3°C / min.

[0160] S5 nanoparticle grafting: the initial modified basalt fiber is immersed in the grafting mixed solution for soaking. After the soaking operation is completed, the excess solution on the surface is removed by blowing, and then a heat treatment operation is performed. After the heat treatment operation is completed, the modified basalt fiber is obtained;

[0161] The grafting mixture is composed of carboxylated nano-silica, ethanol, deionized water, polysorbate-80 and ammonium persulfate, and the weight ratio of carboxylated nano-silica: ethanol: deionized water: polysorbate-80: ammonium persulfate is 4:40:35:0.9:0.3;

[0162] S6 basalt fiber ribbon forming: S6.1 Fiber pre-finishing: Use fiber arrangement equipment to arrange the modified basalt fiber according to the preset density and direction to form a uniform and continuous fiber bundle;

[0163] S6.2 Strip forming process: Use a strip forming device to form the fiber bundle into a strip body with a preset width and thickness to obtain an initial black fiber winding strip;

[0164] In the strip forming processing step, the strip forming equipment is specifically a strip forming calender with a heating function, and the working heating temperature is 40°C; the calendering speed is 2m / min.

[0165] S7: prepare resin liquid: add vinyl ester resin into a container with stirring function, then add methyl ethyl ketone as solvent into the container, start the stirring equipment to perform the first stirring operation, and obtain a basic resin solution; add leveling agent and curing agent into the basic resin solution, and perform the second stirring operation until it is completely blended; then add antioxidant, perform the third stirring operation, and stir until there are no visible particles in the mixed liquid; finally, add antistatic agent into the resin liquid, perform the fourth stirring operation, and stir until it is completely mixed; after the stirring is completed, let it stand for a period of time to allow bubbles to float up and burst naturally, and finally obtain performance-enhanced resin liquid;

[0166] According to the weight ratio, vinyl ester resin: methyl ethyl ketone: leveling agent: antioxidant: antistatic agent: curing agent is 95:15:0.9:0.45:0.18:0.8;

[0167] The leveling agent is polydimethylsiloxane, the antioxidant is tetrakis (2,4-di-tert-butylphenol)-4,4-biphenyl diphosphite; the antistatic agent is distearate methyl ammonium salt antistatic agent; the curing agent is benzoyl peroxide;

[0168] In the first stirring operation, the stirring speed is 200 RPM; in the second stirring operation, the stirring speed is 300 RPM; in the third stirring operation, the stirring speed is 250 RPM; in the fourth stirring operation, the stirring speed is 150 RPM;

[0169] S8 coating and rolling: coating: according to production requirements, the coating machine is used to evenly coat the performance-enhancing resin liquid on the preheated initial black fiber winding tape to obtain the coated black fiber winding tape; the coating machine is equipped with a coating roller to ensure the uniformity of the coating and precise thickness control; the coating machine is equipped with a heating device for preheating the initial black fiber winding tape;

[0170] Post-coating treatment: The coated black fiber winding tape is sent into the pre-curing tunnel for pre-curing treatment. The temperature of the pre-curing tunnel is controlled at 60-80°C and the pre-curing time is 13 minutes.

[0171] Roll making: Use a winding machine to roll the pre-cured coated black fiber winding tape into a roll to obtain a black fiber winding tape roll. Embodiment 2:

[0172] like Figure 1-4 As shown, an application of a black fiber winding tape roll is used, the black fiber winding tape roll prepared in the above embodiment 1 is used, the black fiber winding tape roll is unrolled, and the black fiber winding tape 3 is wound, heated and bonded to the circumferential outer wall of the inner lining layer 1 of the composite pipe as a reinforcement layer 2; the protective layer 4 of the composite pipe is fixed to the outer periphery of the reinforcement layer 2 by extrusion molding; the inner lining layer 1 and the protective layer 4 are both made of thermoplastic resin material; the composite pipe as a whole adopts a fully fused solid wall structure; the specific application steps are as follows:

[0173] A1: Apply adhesive: Before winding, apply a layer of adhesive on the outer wall of the inner liner 1. The diameter of the inner liner 1 is 150 mm.

[0174] A2 Winding: Equipment and Materials: The winding equipment is an automated black fiber winding machine equipped with a high-precision control system that can accurately adjust the winding angle and tension.

[0175] The winding angle is set to ±70°, which provides the best balance between axial and radial strength;

[0176] During the winding process, the overlap of the fiber tape accounts for 30% of the tape width;

[0177] First layer winding: The winding force of the initial layer is set to 40 N. This lower force helps to ensure the initial adhesion between the black fiber winding tape 3 and the surface of the lining layer 1, and avoids deformation or damage of the lining layer due to excessive force.

[0178] Second layer of winding: To enhance the overall stability of the structure, the second layer of winding force is increased to 60 N. This increased force helps to improve the compaction between fibers and the uniformity of the overall structure.

[0179] Third layer of winding: The third layer continues to maintain a winding force of 60 N to further strengthen the existing fiber structure and ensure higher pressure bearing capacity.

[0180] Outermost winding: The outermost winding force is adjusted back to 40 N again. The purpose of this is to reduce stress concentration on the surface and avoid damage caused by external factors during use.

[0181] A3 Curing Treatment: Curing Equipment: Curing Oven: An industrial-grade curing oven designed specifically for composite materials is used, which can provide a uniform and controlled heating environment. The equipment is equipped with a temperature control system that can accurately set and adjust the internal temperature.

[0182] Temperature sensor: There are multiple temperature sensors installed inside the curing oven to monitor the temperature distribution during the curing process. Curing steps: Temperature heating stage: preheat the curing oven to 100°C, and then place the wound composite pipe into the curing oven. After the pipe enters the curing oven, the temperature gradually rises to 140°C;

[0183] Keep warm stage: After reaching the target temperature, maintain this temperature state for 2 hours.

[0184] Cooling stage: After the insulation is completed, the temperature of the curing oven is slowly lowered to avoid thermal stress inside the material caused by rapid cooling.

[0185] Test: Flexibility test: Flexibility is usually measured by the ability of a material to adapt to shape changes when subjected to stress, and one of the important indicators is the minimum bending radius of the material. The smaller the minimum bending radius, the better the flexibility because the material can be bent to a tighter curvature without damage or significant performance degradation. The Xuan fiber wrapped tape and tube made by the specific embodiment one was subjected to a bending test. The minimum bending radius of the DN80 pipe was 1200mm, which is better than the bending radius of 1350mm of glass fiber of the same specification, and has better flexibility. Since the bending radius of 1200mm is less than 1350mm, this shows that the flexibility of the Xuan fiber wrapped tape and tube is better than that of the glass fiber pipe. This means that the Xuan fiber material can withstand tighter bends without damage, and thus has better adaptability to application scenarios in complex or narrow spaces.

[0186] Shear test: measures the shear strength of a material when it is subjected to shear force (i.e. the direction of the force is parallel to the surface of the material). Shear strength is an indicator of the material's ability to withstand shear force, especially in composite materials, which usually involves the bonding strength between layers. Through the shear test of the made Xuan fiber winding tape tube, the shear strength between the reinforcement layers is 42MPa, which is significantly better than that of polyethylene material; polyethylene is a lightweight, corrosion-resistant plastic material commonly used in pipe and container manufacturing. It has good chemical stability and electrical insulation; the shear strength of polyethylene is usually in the range of 10-20 MPa.

[0187] Fatigue test: simulates the behavior of materials under long-term cyclic loads to check the fatigue life and durability of materials after long-term use. This test is critical for evaluating whether the material can withstand long-term dynamic pressure and cyclic load changes. In the second specific embodiment, the fatigue test was carried out on the prepared black fiber winding tube. After 7000 cycles from nominal pressure to zero and then back to nominal pressure, no damage, leakage, delamination and other phenomena occurred.

[0188] Peel strength test: In Example 2, the peel strength between the black fiber winding tape and the inner lining layer was tested to ensure the stability of the bonding interface in high pressure and dynamic environments. The interlayer peel strength test of the black fiber winding tape tube was carried out, and the peel strength was 460N / m, which is better than other fiber materials.

[0189] The embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways without departing from the spirit of the present invention.

Claims

1. A method for preparing a black fiber winding tape roll, characterized in that: The preparation method of the black fiber winding tape roll comprises the following steps: S1 Deep surface cleaning: Use a cleaning solution containing a non-ionic surfactant to clean the basalt fiber raw yarn, and the cleaning temperature is controlled at 50-60°C; after the cleaning operation is completed, rinse with deionized water to obtain cleaned basalt fiber yarn; The nonionic surfactant is at least one of polyoxyethylene alcohol, polyethoxylated nonanoic acid ester and dodecyl polyoxyethylene ether; S2 Fiber surface optimization treatment: Metal impurity removal treatment: The cleaned basalt fiber is immersed in ethylenediaminetetraacetic acid solution for soaking. After the soaking operation is completed, it is rinsed with deionized water until it is neutral to obtain purified basalt fiber; the concentration of ethylenediaminetetraacetic acid solution is 0.3%-0.5%; Active strengthening: immersing the purified basalt fiber in a sodium hydroxide mixed solution for soaking. After the soaking operation is completed, it is rinsed with deionized water until it is neutral to obtain pretreated basalt fiber filaments; The sodium hydroxide mixed solution contains an auxiliary agent, which is one of polysorbate-20 and dodecyl polyoxyethylene ether; the concentration requirements of the auxiliary agent are as follows: the concentration of polysorbate-20 is 0.08%-0.2%; the concentration of dodecyl polyoxyethylene ether is 0.1%-0.2%; S3: preparing a coupling agent solution: mixing ethanol and deionized water evenly, using the mixture as a solvent, adding a coupling agent to the solvent and stirring the mixture evenly, adding an acidic catalyst, and continuing to stir the mixture until the mixture is evenly mixed to obtain a coupling agent solution; The coupling agent is γ-methacryloxypropyltrimethoxysilane; The acid catalyst is hydrochloric acid; S4 coupling agent-mediated surface modification: the pretreated basalt fiber is immersed in deionized water for wetting, and the wetted basalt fiber is transferred to a solution containing a coupling agent for immersion. After the immersion, the excess solution on the surface is removed by blowing, and then a heat treatment is performed. After the heat treatment, the initial modified basalt fiber is obtained. S5 nanoparticle grafting: the initial modified basalt fiber is immersed in the grafting mixed solution for soaking. After the soaking operation is completed, the excess solution on the surface is removed by blowing, and then a heat treatment operation is performed. After the heat treatment operation is completed, the modified basalt fiber is obtained; The grafting mixed solution is composed of carboxylated nano-silica, ethanol, deionized water, polysorbate-80 and ammonium persulfate, wherein the weight ratio of carboxylated nano-silica: ethanol: deionized water: polysorbate-80: ammonium persulfate is 3-4: 40-50: 35-40: 0.8-1.2: 0.3-0.4; S6 basalt fiber ribbon forming: S6.1 Fiber pre-finishing: Use fiber arrangement equipment to arrange the modified basalt fiber according to the preset density and direction to form a uniform and continuous fiber bundle; S6.2 Strip forming process: Use a strip forming device to form the fiber bundle into a strip body with a preset width and thickness to obtain an initial black fiber winding strip; S7: prepare resin liquid: add vinyl ester resin into a container with stirring function, then add methyl ethyl ketone as solvent into the container, start the stirring equipment to perform the first stirring operation, and obtain a basic resin solution; add leveling agent and curing agent into the basic resin solution, and perform the second stirring operation until it is completely blended; then add antioxidant, perform the third stirring operation, and stir until there are no visible particles in the mixed liquid; finally, add antistatic agent into the resin liquid, perform the fourth stirring operation, and stir until it is completely mixed; after the stirring is completed, let it stand for a period of time to allow bubbles to float up and burst naturally, and finally obtain performance-enhanced resin liquid; According to the weight ratio, vinyl ester resin: methyl ethyl ketone: leveling agent: antioxidant: antistatic agent: curing agent is 95-98:15-17:0.8-1:0.45-0.5:0.18-0.2:0.7-1; The leveling agent is polydimethylsiloxane, the antioxidant is tetrakis (2,4-di-tert-butylphenol)-4,4-biphenyl diphosphite; the antistatic agent is a quaternary ammonium salt antistatic agent; the curing agent is benzoyl peroxide; S8 coating and rolling: coating: according to production requirements, the coating machine is used to evenly coat the performance-enhancing resin liquid on the preheated initial black fiber winding tape to obtain the coated black fiber winding tape; the coating machine is equipped with a coating roller to ensure the uniformity of the coating and precise thickness control; the coating machine is equipped with a heating device for preheating the initial black fiber winding tape; Post-coating treatment: The coated black fiber winding tape is sent into the pre-curing tunnel for pre-curing treatment. The temperature of the pre-curing tunnel is controlled at 60-80°C. Roll making: Use a winding machine to roll the pre-cured coated black fiber winding tape into a roll to obtain a black fiber winding tape roll.

2. The method for preparing the black fiber winding tape roll according to claim 1, characterized in that: In step S1, the parameter requirements of the basalt fiber precursor are as follows: silicon dioxide content is 52-54%; aluminum oxide content is 12-15%; calcium oxide content is 9-11%; magnesium oxide content is 9-10%, and the total content of ferrous oxide and ferric oxide is 12-13%; titanium dioxide content is 1.5-2%; the total content of sodium oxide and potassium oxide is not higher than 1%; diameter is 10-12 microns; tensile strength is not less than 3.5GPa, and elongation at break is not less than 3.5%.

3. The method for preparing the black fiber winding tape roll according to claim 1, characterized in that: In step S2, in the metal impurity removal treatment step, the temperature of the EDTA solution is 35-45° C.; the immersion time is 20-30 minutes; The pH value of the sodium hydroxide mixed solution is 11-13; After the fiber surface optimization treatment, the contact angle of the pretreated basalt fiber is required to be less than 30°.

4. The method for preparing the black fiber winding tape roll according to claim 1, characterized in that: In step S3, the pH value of the coupling agent solution is 4-5; in the coupling agent solution, the concentration of the coupling agent is 3%-5%; in the solvent, the weight ratio of ethanol: water is 7:2-3.

5. The method for preparing the black fiber winding tape roll according to claim 1, characterized in that: In step S4, in the air blowing method, the specific requirements are as follows: distance height: 5-10 cm; angle: nozzle 30-45°; nozzle distribution: multiple nozzles are arranged horizontally and evenly distributed above or on both sides of the fiber; The requirements for the heat treatment operation are as follows: at the beginning, heat from room temperature to 100-120°C, and control the heating rate at 2-5°C / min. Use thermogravimetric analysis technology to continuously monitor the heat treatment process. When the mass loss curve tends to be stable and there is no further mass loss, end the heat treatment and reduce the temperature to room temperature. The cooling rate is controlled at 2-5°C / min.

6. The method for preparing the black fiber winding tape roll according to claim 1, characterized in that: In step S5, the requirements for the heat treatment operation are as follows: at the beginning, heating is performed from room temperature to 110-120°C, the heating rate is controlled at 2-3°C / min, and the heat treatment process is continuously monitored using thermogravimetric analysis technology. When the mass loss curve tends to be stable and there is no further mass loss, the heat treatment is terminated and the temperature is reduced to room temperature, and the cooling rate is controlled at 2-3°C / min.

7. The method for preparing the black fiber winding tape roll according to claim 1, characterized in that: In step S6, in the fiber pre-finishing step, the fiber arrangement device is specifically an automated fiber arrangement machine; arrangement density: 0.1-0.5 mm; arrangement direction: parallel to the forward direction of the belt-shaped forming device to reduce the crossing and entanglement between fibers; speed control: the arrangement speed is synchronized with the forming speed to ensure the continuous supply and uniform distribution of fibers; In the strip forming processing step, the strip forming equipment is specifically a strip forming calender with a heating function, and the working heating temperature is 40-50°C; the calendering speed is 1-3m / min.

8. The method for preparing the black fiber winding tape roll according to claim 1, characterized in that: In step S7, in the first stirring operation, the stirring speed is 100-300 RPM; in the second stirring operation, the stirring speed is 200-400 RPM; in the third stirring operation, the stirring speed is 150-350 RPM; in the fourth stirring operation, the stirring speed is 100-300 RPM; In step S8, the pre-curing treatment time is 10-15 minutes.

9. An application of a black fiber winding tape roll, the black fiber winding tape roll is prepared by the preparation method of the black fiber winding tape roll according to any one of claims 1 to 8; characterized in that: Unroll the Xuan fiber winding tape, and heat and bond the Xuan fiber winding tape to the circumferential outer wall of the inner lining layer of the composite pipe as a reinforcement layer; the protective layer of the composite pipe is fixed to the outer circumference of the reinforcement layer by extrusion molding; the inner lining layer and the protective layer are both made of thermoplastic resin materials; the composite pipe as a whole adopts a fully fused solid wall structure; the specific application steps are as follows: A1: Apply adhesive: Before winding, apply a layer of adhesive on the outer wall of the inner lining layer; A2 winding: Use the black fiber winding tape to wrap around the circumferential outer wall of the inner liner coated with adhesive; the overlap during winding accounts for 20%-50% of the bandwidth; A3 Curing treatment: After winding, curing treatment is carried out, and the curing temperature is 100-140°C.

Citation Information

Patent Citations

  • Nano modified soaking agent used for basalt fiber

    CN104926158A

  • Preparation method and application of basalt fiber surface nano-coated multi-scale reinforcement

    CN107200867A